2007
DOI: 10.1007/s00109-007-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Overactivity of the intestinal endocannabinoid system in celiac disease and in methotrexate-treated rats

Abstract: The endocannabinoid system is upregulated in both human inflammatory bowel diseases and experimental models of colitis. In this study, we investigated whether this upregulation is a marker also of celiac disease-induced atrophy. The levels of the cannabinoid CB(1) receptor, of the endocannabinoids, anandamide, and 2-arachidonoyl-glycerol (2-AG), and of the anti-inflammatory mediator palmitoylethanolamide (PEA) were analyzed in bioptic samples from the duodenal mucosa of celiac patients at first diagnosis asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 36 publications
6
67
0
1
Order By: Relevance
“…Nevertheless, there is still little evidence on the contribution of endocannabinoids in celiac disease, a chronic inflammation of the small bowel induced in genetically susceptible individuals by an environmental irritant, gluten, with the possible participation of other environmental cofactors [9]. In particular, there is only one study showing higher AEA levels in the duodenal mucosa of active celiac patients in comparison to treated celiac patients and controls [10]. In the present study, we aimed to explore AEA metabolism by investigating mRNA, protein and activity of enzymes responsible for the synthesis (N-acylphosphatidyl-ethanolamine specific phospholipase D, NAPE-PLD) [11] and degradation (fatty acid amide hydrolase, FAAH) [12] of AEA in the duodenal mucosa of untreated celiac patients, celiac patients on a gluten-free diet and control subjects.…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, there is still little evidence on the contribution of endocannabinoids in celiac disease, a chronic inflammation of the small bowel induced in genetically susceptible individuals by an environmental irritant, gluten, with the possible participation of other environmental cofactors [9]. In particular, there is only one study showing higher AEA levels in the duodenal mucosa of active celiac patients in comparison to treated celiac patients and controls [10]. In the present study, we aimed to explore AEA metabolism by investigating mRNA, protein and activity of enzymes responsible for the synthesis (N-acylphosphatidyl-ethanolamine specific phospholipase D, NAPE-PLD) [11] and degradation (fatty acid amide hydrolase, FAAH) [12] of AEA in the duodenal mucosa of untreated celiac patients, celiac patients on a gluten-free diet and control subjects.…”
Section: Introductionmentioning
confidence: 93%
“…Additional and pharmacologically relevant targets of PEA action include PPARα (Lo Verme et al, 2005;O'Sullivan and Kendall, 2010) and transient receptor potential vanilloid type-1 (TRPV1) channels (De Petrocellis et al, 2001;Ambrosino et al, 2013; channel nomenclature follows Alexander et al, 2013b), which have been identified in peripheral nerves controlling intestinal motility (Boesmans et al, 2011;Holzer, 2011). PEA has been identified in the rodent Fu et al, 2007;Izzo et al, 2010;2012;Diep et al, 2011;Balvers et al, 2013) and human (Darmani et al, 2005;D'Argenio et al, 2007;Zhang et al, 2014) digestive tract. When given exogenously, PEA reduces gastrointestinal transit and displays anti-inflammatory effects in the gut (Di Paola et al, 2012;Petrosino et al, 2013;Esposito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…8 Çölyak hastalarında duodenumdan alınan biyopsilerde 2-AG düzeyi değişmez iken, AEA seviyesinin arttığı, glutensiz diyet tedavisi sonrası ise AEA seviyesinin normale döndüğü gözlen-miştir. 9 Kolon poliplerinde ve kolorektal kanser hastalarından alınan kolon biyopsilerinde hem 2-AG hem de AEA seviyelerinde anlamlı artış olduğu göz-lenmiştir. 10 Diğer bir çalışmada ise divertikülozis koli olan hastaların kolon dokusunda AEA seviyelerinin arttığı, 2-AG düzeyinin ise azaldığı saptanmıştır.…”
Section: Gastroi̇ntesti̇nal Si̇stemde Kannabi̇noi̇d Si̇stemunclassified